Interaksi Sosial dalam Membentuk Julukan Pada Mahasiswi Perokok: Studi Pada Fakultas Ilmu Sosial Universitas Negeri Gorontalo - Hadju, Khalisah Rahmadina; Dano Putri, Citra F.I.L; Mariana, Feni (Jambura Jurnal Ilmu Komunikasi, 2025)
This study analyzes the social interaction process among female student smokers in forming nicknames within the Faculty of Social Sciences at Universitas Negeri Gorontalo. Smoking among female individuals, particularly female students, is often perceived as deviating from prevailing social norms and is frequently subject to negative stigma and labeling. This study employs a descriptive-qualitative method using symbolic interactionism and nicknaming theories to explore the social dynamics involved in nickname formation. The data are collected from six informants, consisting of three female students who actively smoke and three male students from the same circle. The findings show that social interactions among smokers create a safe space and serve as a medium for group identity formation, which also contributes to the emergence of behavior-based nicknames. These nicknames aries through daily interactions, jokes, and social perceptions, which are then internalized as part of the group’s social dynamics. These findings revea that social interaction plays a crucial role in shaping meaning toward deviant behavior and the social identity of individuals within the academic environment.